21st Century Literacy Skill of Information Technology and Computer Education Students - Sulistiyarini, Dewi; Sabirin, Febrianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study aims to determine student perceptions related to technology and media literacy in the Information Technology and Computer Education (ITC Education) Program and to compare technology and media literacy based on the students’ level and gender. The method used in this research is a survey method with data collection tools in the form of questionnaires and analysis using descriptive and comparative analysis. The population of this study were all 696 students of Information Technology and Computer Education and the sample of this study was 236 taken using the Proportionate Stratified Random Sampling technique. The results showed that the technology and media literacy of ITC Education students belong to the quite good category. In this research, it is known that there are significant differences in technology and media literacy based on gender, while based on the level of students there are significant differences in media literacy but there is no difference in technology literacy.